Rooftop PV Plant Development Planning at the Central Java Provincial DPRD Secretariat Office - Andrian Mayka Ariawan; Jaka Windarta; Sujarwanto Dwiatmoko (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2022)
Central Java Province targets the achievement of the new and renewable energy (EBT) portion in the energy mix by 2030 at 22.55%. In order to achieve this target, the Central Java Provincial Government has consistently developed the use of EBT, one of which is through the construction of rooftop solar power plants (Rooftop PV Plant) in government buildings. In addition to requiring a fairly high initial investment cost, the construction of a Rooftop PV plant connected to the PT. PLN (Persero) requires a fairly complicated process, so proper planning must obtain optimal results. This paper will discuss an example of a Rooftop PV Plant development plan at the Secretariat Office of the Central Java Provincial DPRD, including the use of electrical energy prior to the installation of a Rooftop PV Plant; an analysis of the condition and availability of the location; the design and system of a Rooftop PV Plant; an estimate of the total potential energy that can generate; the investment costs of a Rooftop PV Plant; as well as evaluating the results of using Rooftop PV Plant. The electricity bill at the Central Java Provincial DPRD Secretariat Office prior to installing Rooftop PV Plant is Rp. 91.308.323,- per month. The recommended PV design, built on an area of ​​197 m2, is a rooftop on-grid PV Plant system with 6 PV arrays, each of which PV arrays are installed with as many as 20 solar modules arranged in series. The total number of solar modules installed is 120 solar modules with a total capacity equivalent to 30 kWp. Based on the simulation results using the PVSyst 6.4.3 software, the Rooftop PV Plant system can generate electrical energy of up to 43,420kWh per year or equivalent to 118.9kWh per day with a performance ratio of 79.4%. The potential for saving electricity costs from the simulation results can reach Rp. 4,034,441.- per month. The results of the evaluation of the utilization of the Rooftop PV Plant through the recording of the inverter monitoring system within 1 (one) year after installation shows the amount of electrical energy produced is 40,558 kWh, so that the manager of the Secretariat of the DPRD Central Java Province office can save a budget of Rp. 3,768,514.- per month from the use of the Rooftop PV Plant. This figure is not much different from the simulation results at planning. There is a difference in the cost savings of electricity payments at the Central Java Provincial DPRD Secretariat Office during 2020 of Rp. 4,493,300,- excluding savings due to the use of Rooftop PV Plant due to implementing the work from home (WFH) system during the COVID-19 pandemic, which resulted in a significant reduction in the use of electrical energy.